Aspects Related to Ship Collision: Basis and Consequences of Applicable Laws - Susdarwono, Endro Tri (Jurnal Ilmiah Kemaritiman Nusantara, 2022)
This study aims to provide a description related to the legal basis and legal consequences that arise and are imposed on ship accidents in the form of ship collisions. This research is classified as normative law research using secondary data. The type of research is descriptive explanatory with the problem approach used is an analytical normative approach to legal substance (approach of legal content analysis). The data used in this study is secondary data consisting of primary and secondary legal materials. The data collection carried out in this research is a literature study. Ship collision can be defined as a marine disaster which is the source of losses incurred by one party or both parties, and the legal consequences arising from the ship collision are regulated in Chapter VI, Second Book of the KUHD Articles 534 – 544. The ship owner is responsible in the event of a ship colliding. However, what must be considered in this case, in accordance with Article 535 of the KUHD, must meet the criteria to be called a ship collision. In the event of a ship colliding, the principle of whoever is at fault is the one who is responsible. For this reason, the loss suffered by the other party, the ship owner resulting in a ship collision must pay compensation to the ship owner affected by the collision.